Lymphatic Clearance of the Brain: Perivascular, Paravascular and Significance for Neurodegenerative Diseases - Bakker, Erik N. T. P. (Cell Mol Neurobiol, 2016)
The lymphatic clearance pathways of the brain are different compared to the other organs of the body and have been the subject of heated debates. Drainage of brain extracellular fluids, particularly interstitial fluid (ISF) and cerebrospinal fluid (CSF), is not only important for volume regulation, but also for removal of waste products such as amyloid beta (Aβ). CSF plays a special role in clinical medicine, as it is available for analysis of biomarkers for Alzheimer’s disease. Despite the lack of a complete anatomical and physiological picture of the communications between the subarachnoid space (SAS) and the brain parenchyma, it is often assumed that Aβ is cleared from the cerebral ISF into the CSF. Recent work suggests that clearance of the brain mainly occurs during sleep, with a specific role for peri- and para-vascular spaces as drainage pathways from the brain parenchyma. However, the direction of flow, the anatomical structures involved and the driving forces remain elusive, with partially conflicting data in literature. The presence of Aβ in the glia limitans in Alzheimer’s disease suggests a direct communication of ISF with CSF. Nonetheless, there is also the well-described pathology of cerebral amyloid angiopathy associated with the failure of perivascular drainage of Aβ. Herein, we review the role of the vasculature and the impact of vascular pathology on the peri- and para-vascular clearance pathways of the brain. The different views on the possible routes for ISF drainage of the brain are discussed in the context of pathological significance.